A plica ción de la conta bilida d comercia l en Autorepuestos Korea Motors de la ciudad de Santa Rosa, provincia de el Oro, periodo mayo junio del 2016 - Pambi Pambi., Mónica Elizabeth (2017)
This work is fully justified as it will be meeting the requirements to obtain the degree in Accounting and Auditing, in order to strengthen the knowledge acquired in such prestigious institution, in addition the owner of Autorepuestos Korea Motors may have adequate control of its operations; the same ones that are reflected in the good service that it will offer to its clients and to the community in general, contributing in this way to the economic development of the city and therefore of the country. Complying with the objectives began with the design of the Plan and the Accounts Manual, according to the requirements of the company, then the supporting documentation was collected, which allowed the preparation of the operations memorandum, the State of Initial Situation, Daily Book, General Ledger, Verification Balance, Worksheet and auxiliary documents such as payment roles, purchase and sales journal. Once the accounting process of the operations carried out, it was possible to determine through the Commercial Accounting the results achieved, which are reflected in the Income Statement, Statement of Financial Position and Cash Flow; which reflected the utility during the study period. Finally, it is concluded that the company under study has an accounting process in accordance with the Accounting Rules and Principles and the Tax Regulations that enhanced and veracity the Financial Statements, which is recommended that the company proceed to host the present investigative work in order to improve their economic activities.